Lasalocid Poisoning in Buffalo Calves in the State of Pará, Brazil - Barbosa Neto, José Diomedes; Chaves Oliveira, Carlos Magno; Domiciano, Tarcísio Oliveira; Oliveira, Mariana Correia; Pires, Ana Paula de Castro; Brito, Marilene de Farias; Malafaia, Pedro (Acta Scientiae Veterinariae, 2021)
Background: Ionophore antibiotics are food additives with coccidiostatic or antimicrobial action; they are also used as growth promoters, ruminal pH regulators, volatile fatty acid molar modifiers, and methanogenesis reducers. However, these compounds have the potential to cause microbial resistance, in addition to the risk of intoxication. Ionophore poisoning may be caused by excessive intake, sensitivity of certain animal species, and concomitant use with other drugs. In Brazil, cases of ionophore poisoning in buffalos are rare. This study aims to describe the epidemiological, clinical, and pathological findings of lasalocid poisoning in buffalo calves. Case: A visit was made to a farm in the municipality of Mojú, Pará state to care for Murrah buffalo calves. After weaning, the buffalos were grazed in paddocks with Panicum spp., and received a supplement of mineral, protein, and vitamin. This supplement contained, per kg, 250 g PB, 50 g Ca, 20 g P, 8 g S, 39 g Na, 20 mg Co, 557 mg Cu, 200 mg Fe, 12.4 mg Se, 2040 mg Zn, 0.19 mg biotin, 26750 IU of vitamin A, 4175 IU of vitamin D, 155 IU of vitamin E and 300 mg/kg of lasalocid. The product was made available to all calves, at 1-2 g/kg body weight (BW), according to the manufacturer’s recommendations. Older calves were raised together with those less than 30 days old; as a result, the older calves tended to eat more, which could lead to a supplementation consumption of more than 1 kg body weight per animal per day. It was reported that between 40 and 60 days after the introduction of this supplement, 16 calves fell ill and died due to apathy, motor instability, tremors, and distended neck. The herd had a mortality rate of 33.3%. Two calves underwent a necroscopic examination at the Pathology Section of the Veterinary Institute of the Federal University of Pará. Macroscopic examination revealed extensive pale areas in the skeletal muscles, myocardium, and tongue. Fragments of these muscles and various organs were collected, fixed in 10% buffered formalin, processed according to the routine histological technique, and stained with hematoxylin-eosin and Masson’s trichrome stain. Microscopic examination of the histologic samples revealed foci of muscle atrophy and necrosis characterized by an increase in cytoplasmic eosinophilia associated with the loss of stretch marks, and hyperchromatic nuclei that were displaced to the periphery. The necrosis of the muscle fibers was highlighted by Masson’s trichrome staining. Discussion: The diagnosis of lasalocid poisoning in buffalo calves was based on epidemiological data, clinical findings, results of macroscopic and histopathological examination, and based on the estimated ionophore intake, obtained directly from the supplement label and by the calf’s handler. Based on the absence of stratification of the calves by similarity of age and because the buffalo calves older than 30 days could eat more than 1 kg of the supplement (containing 300 mg/kg of lasalocid), it was possible to estimate the intake of lasalocid per kg CP (body weight). Therefore, the intake of lasalocid by a 70-kg buffalo calf in approximately 90 days and daily supplement consumption between 1 and 1.5 kg would be between 4.2 and 6.4 mg/kg of body weight. This report reinforces that notion that buffalo calves should never ingest ionophores; however, if necessary, strict protocols must be followed to avoid poisoning in these animals. This study highlighted the fact that stratification of buffaloes by different age groups during feeding became a risk factor that allowed greater consumption by older animals; this led to the estimated consumption of 4.2-6.4 mg/kg of lasalocid. Keywords: ionophores, ruminants, buffalo calves, muscle necrosis. Descritores: ionóforos, ruminantes, bezerros búfalos, necrose muscular. Título: Intoxicação por lasalocida em bezerros búfalos no Estado do Pará, Brasil